2020
DOI: 10.1101/2020.01.27.20018770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial contributions to oxalate metabolism in health and disease

Abstract: Over-accumulation of oxalate in humans may lead to nephrolithiasis and nephrocalcinosis. Humans lack endogenous oxalate degradation pathways (ODP), but intestinal microbiota can degrade oxalate and protect against its absorption. However, the particular microbes that actively degrade oxalate in vivo are ill-defined, which restricts our ability to disentangle the underlying taxonomic contributions. Here we leverage large-scale multi-omics data (>3000 samples from >1000 subjects) to show that the human mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…However, the genes encoding FCR and OXC were substantially more prevalent and more abundant than the genes encoding oxalate oxidase and decarboxylase in the gut. Among the 660 subjects, OXC can be detected in the metagenome of 554 subjects (84%) and FCR can be detected in 581 subjects (88%) (Liu et al, 2020). These data suggested that OMBS with OXC and FCR are the predominant bacteria in the healthy human gut.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the genes encoding FCR and OXC were substantially more prevalent and more abundant than the genes encoding oxalate oxidase and decarboxylase in the gut. Among the 660 subjects, OXC can be detected in the metagenome of 554 subjects (84%) and FCR can be detected in 581 subjects (88%) (Liu et al, 2020). These data suggested that OMBS with OXC and FCR are the predominant bacteria in the healthy human gut.…”
Section: Discussionmentioning
confidence: 84%
“…Oxalate decarboxylases and oxalate oxidases are members of the cupin superfamily of proteins and the two enzymes show high similarity at the amino acid level (Burrell et al, 2007). The genes encoding the four enzymes were widely present in the healthy gut microbiome on the basis of the analysis of 660 subjects (Liu et al, 2020). However, the genes encoding FCR and OXC were substantially more prevalent and more abundant than the genes encoding oxalate oxidase and decarboxylase in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis of 660 subjects, the four genes encoding the enzymes were widely present in the healthy gut microbiome [39]. In the metagenomes of 660 subjects, Oxc can be detected in 554 (84%) and Frc in 581 (88%).…”
Section: Analysis Of Transcription and Function Of The Oxc And Frc Ge...mentioning
confidence: 99%